Appending the enforcement clause of the redress of damage stated in the Article 72 § 2 of the Code of Criminal law - Pilarczyk, Łukasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The study aims on selected problems associated with appending the enforcement clause on the redress of damage in Polish Criminal law. The difference between the redress of damage as a penal measure and as a probationary measure outlined by The Polish Supreme Court is significant for the analysed perspective. The author indicates that the Supreme Court claims, that a probationary measure enforcement clause could be put on the redress of damage only after the expiration of a period of time appointed by the court to the perpetrator to compensate for the harm caused by a crime. Due to the outlined interpretation by the Polish Supreme Court the author finds the presented statement as not rightful due to the wrong interpretation of the law and flagrant infringement of rights of the victims of the crimes.